URGENSITAS PENGKAJIAN ISLAM SECARA INTERDISIPLINER - Edi Kuniawan Farid (Jurnal Inovasi Penelitian, 2021)
The development of technology that have an impact on life lead to various problems. In this case, religion is expected to be a solution to the problems of human life. However, the stagnation in the Islamic world that is felt by some Muslim scientists requires a way out, so that Islam can answer all the challenges of life at all times. This is where the urgency of an interdisciplinary Islamic studies. A progressive-comprehensive study of Islam. A Comprehensive study in which there is no fragmentation which results in literal-textual thinking. A progressive study in which Islam is a religion that is sholih li kulli zaman wal makan so that it is able to answer currents problems even in the future.